Antithyroid Antibodies and Thyroid Function in Pediatric Patients with Celiac Disease - Derya Kalyoncu; Nafiye Urganci (International Journal of Endocrinology)
Objective. Aim of the study was to determine the prevalence of autoimmune thyroid disease, persistence of antithyroid antibodies, effect of gluten-free diet, and long-term outcome of thyroid function in pediatric patients with celiac disease (CD). Methods. 67 patients with CD aged from 1 year to 16 years were screened for thyroid antithyroperoxidase, antithyroglobulin and anti-TSH receptor antibodies, serum free triiodothyronine, free thyroxine, and thyroid-stimulating hormone (TSH) at diagnosis and during follow-up. Results. None of the patients had antithyroid antibodies at diagnosis. Antithyroid antibodies became positive in 16.4% of the patients (11/67) 2 to 3 years after the diagnosis of CD. Clinical hypothyroidism was observed only in 3 of 11 CD patients with positive antithyroid antibodies (27.2%). The antithyroid antibodies positive and negative patients did not differ significantly according to compliance to GFD (P>0.05). A statistically significant difference was observed only in age, in which the patients with positive antithyroid antibodies were younger than the patients with negative antithyroid antibodies (P=0.004). None of the patients had any change in their thyroid function and antibody profile during their follow-up. Conclusion. Antithyroid antibodies were detected in younger pediatric patients with CD and the prevalence of antithyroid antibodies did not correlate with the duration of gluten intake.